Analisa Alat Kendali Suhu dan Kelembaban berbasis Arduino Mega 2560 - Ari Yuliati; Cecep Gumilar; Yovi Manova (Pusat Teknologi Informasi dan Pangkalan Data IAIN Syekh Nurjati Cirebon, 2022)
Temperature and humidity control systems are widely applied in agriculture. To increase crop yields and make it easier for agricultural actors, especially in plant cultivation, it is important to innovate in the development of technology that is growing rapidly. This study aims to analyze the level of validity and reliability of temperature and humidity control devices in a cultivation test room based on Arduino Mega 2560 with the help of SPSS. The results of the analysis and test of temperature and humidity control devices, with a maximum coefficient of variation of 1.86% and a minimum reliability coefficient of 0.62.